Proverbs against empire: Heteroglossia and decolonial realism in Achebe’s Things Fall Apart - Shalghin, Akram H; Saleh, Shoeb; AlAli, Rommel Mahmoud; Zaher, Ashraf M; Abdul Wahab, Mohammad Osman; Almoisheer, Reem Abdulaziz (Research Journal in Advanced Humanities, 2026)
This article argues that proverbs in Chinua Achebe’s Things Fall Apart are not ornamental traces of orality or ethnographic markers of “authentic” African culture. They are structural to the novel’s politics of form. Read through a revised Bakhtinian account of heteroglossia and a decolonial understanding of realism, proverbial discourse emerges as a mode of social reasoning, ethical deliberation, political memory, and narrative world-making. Achebe uses proverbs to stage internally differentiated forms of Igbo speech while opposing them to the flattening languages of missionary abstraction, colonial law, and imperial archive. The article shows that proverbial speech operates at three interconnected levels: as social jurisprudence within Umuofia, as a formal device that multiplies ideological accents within the novel, and as an anti-imperial strategy for remaking English into a medium adequate to African historical experience. At the same time, the novel does not idealize precolonial life: it exposes the gendered and hierarchical limits of proverbial authority. The result is a decolonial realism grounded in plurality rather than ethnographic summary.